Effect of Tandospirone on Sleep Latency in Rats Placed on a Grid Suspended Over Water - Yoshiaki Utsu; Kazuaki Shinomiya; Shin Tokunaga; Asae Ohmori; Chiaki Kamei (Elsevier, 2007)
The present study was performed to examine the effect of tandospirone on sleep latency in a new insomnia animal model by placing rats on a grid suspended over water. For investigating the mechanism of tandospirone, the effect of tandospirone on sleep latency was also studied using rats that were depleted with neuronal serotonin (5-HT) after p-chlorophenylalanine administration. Tandospirone caused a shortening of sleep latency dose-dependently, and a significant effect was observed at 20 mg/kg, p.o. or more. A shortening of sleep latency was observed by administration of p-chlorophenylalanine (300 mg/kg, i.p.) for 2 days. On the other hand, tandospirone exerted no potentiating effect on the shortening of sleep latency induced by p-chlorophenylalanine. From these findings, a shortening of sleep latency induced by tandospirone may occur through the pre-synaptic 5-HT1A receptors in rats. Keywords:: tandospirone, sleep latency, sleep disturbed model, antianxiety, 5-HT1A receptor